Attachment in the Making: Mother and Father Sensitivity and Infants’ Responses during the Still-Face Paradigm - Braungart-Rieker, Julia M. (2014)
This study examined the extent to which infant and parent response trajectories during the Still-Face-Paradigm (SFP) in early infancy predicted later infant-mother and infant-father attachment. Families (n = 135) participated in the SFP when infants were 3, 5, and 7 months and the Strange Situation when infants were 12 (mothers) and 14 months (fathers). Multilevel models showed that parent sensitivity assessed during the SFP was related to infants’ affective and behavioral response trajectories during the SFP, and that sensitivity and infant response trajectories predicted attachment. Results from the present study support the notion that parent and infant responses in the SFP with mothers and fathers during Bowlby’s Attachment in the Making phase provide insight into the developing parent-child attachment relationship.